AN ALTERNATIVE CREDIT GUARANTEE SCHEME FOR FINANCING MSEs IN ISLAMIC BANKING - M. Luthfi Hamidi; Fikri Salahudin (Journal of Islamic Monetary Economics and Finance, 2021)
The objective of this paper is to propose a model for a financing guarantee scheme (FGS) funded by the voluntary sector (through zakat, infaq, and sadaqah, or ZIS funds) to support small and medium-sized enterprises (SMEs). We argue that the existing credit guarantee scheme (CGS) relies on government funding, but that in the current Covid-19 pandemic it is experiencing unstable financial capability. Hence, the sustainability of the CGS program is questionable. We employ the input-output (I-O) approach to identify the expected impact if the proposed FGS is applied. We further substantiate the proposal with seven Indonesian Syariah experts’ opinions, of whom five suggest that the alternative scheme is acceptable. The simulation using I-O shows that if IDR1 trillion (out of IDR10 trillion from ZIS funds in 2019) is disbursed through the scheme, this will increase economic growth by 0.0117%, representing economic activities worth IDR1.235 trillion, and creating 2,151 new jobs. We further discuss the implications of the findings for the Islamic banking industry in the future and for regulators.